The interaction of precipitation and land use effect on biological and chemical soil health indicators across a Kansas precipitation gradient - Poydras, Tiffany (Kansas State University, 2024)
As a concept and principal, soil health is intricately entwined with climate change. The health and stability of the soil is vital to reducing agricultural CO2 emissions and increasing sequestered carbon to combat climate change. To improve the effectiveness of soil health practices, it is essential that thorough investigations be made on the interactions between soil health principles in climate change as well as how responses can change with different land uses and increasing depth. Analysis of the effect of temperature, elevation, water content, and seasonal variability have been thoroughly explored, but the legacy that precipitation has on soil health in different land uses has been widely looked over. Conveniently, Kansas is the perfect place for this investigation because it has a rather consistent soil-type, land formation and a grassland ecosystem with a linear precipitation gradient. To test this relationship, three different land uses were sampled, representing three different levels of disturbance (Native Prairie, Restored Prairie, and AG) across 12 different locations, creating a linear gradient increasing from west to east from 400 mm to 1100 mm of mean annual precipitation. These sites were sampled to a depth of 120 cm and divided into five depth increments of 0-5 cm, 5-15 cm, 15-30cm, 30-75cm, and 75-120cm. Analysis of soil was conducted using soil health indicators, including soil organic carbon, total nitrogen, enzyme activity, PLFA, and CO2 respiration. Statistical analysis was performed in R using both univariate and multivariate statistical models to show the complex interaction between factors. Results show that disturbance impacted the relationship between soil health even after restoration, and sites with active agricultural use were decoupled from the effects of precipitation.
Keywords: Climate change; Soil health; Native prairie; Restored prairie; Precipitation gradient; Carbon